Economic Value of Agarwood and Its Prospects of Cultivation - Adhikari, Suraj Raj; Pokhrel, Kusum; Baral, Sunil Dutta (International Journal of Applied Sciences and Biotechnology, 2021)
Aquilaria are genera of tropical trees that produces a valuable resinous wood called agarwood. Agarwood plant have been widely used as traditional medicines and Ayurvedic medicine. They are used for the treatment of arthritis, asthma, diarrhoea etc effects. It contains bioactive phytochemical sesquiterpenoids, 2 (-2-phenylethyl)-4H-chromen-4-one derivatives, genkwanins, mangiferins, cucurbitacins, other terpenoids and phenolic acids. Many pharmacological studies have been performed on anti-allergic, anti-cancer, anti-inﬂammatory, anti-microbial, anti-diabetic, anti-oxidant, etc. The aromatic properties of agarwood when burned or distilled are extraordinary and there is high demand for the resinous wood to make incense, perfume and as traditional medicine. Aquilaria are native to northern India but over harvesting of this tree as well as other forest trees in the past has ravaged the hill country. With new technology that has been developed to induce agarwood in trees, it is now possible to produce a sustainable high valued agarwood in young plantation trees. The growing of Aquilaria in the hill agro-ecosystems of Nepal and cultivation of agarwood as a crop using new technology could provide a new economy for the region. Int. J. Appl. Sci. Biotechnol. Vol 9(1): 23-31